Palladium-catalyzed anti-michael reductive heck reaction of α,β-unsaturated esters - Guo, Tao (2022)
A general intermolecular anti-Michael reductive Heck reaction of α,β-unsaturated esters with organobromides has been developed. Most topical classes of aryl, heteroaryl, and vinyl bromides were found to efficiently react with a variety of internal conjugated alkenes. This protocol set up a platform toward diverse α-arylated 1,6-dicarbonyl frameworks found in natural products and drugs, which are still highly challenging targets in traditional α-arylation protocols because of competitive selectivity of enolation. A removable directing group, gram-scale reaction, and modification of complex molecules have additionally demonstrated that the anti-Michael reductive Heck reaction is a powerful complementary strategy to the classical α-arylation approaches. Preliminary mechanistic studies are consistent with our proposed mechanistic design.